Synthesis of Copper Nanoparticles at Room Temperature Using Hydrazine in Glycerol - Khan, Maksudur R.; Ong, Huei Ruey; Ridzuan, Ramli; R. M., Yunus (Trans Tech Publications Inc., 2014)
Copper nanoparticles (CuNPs) have been prepared by the reduction of copper chloride in glycerol using hydrazine at ambient conditions. The reduction process takes place under vigorous stirring for 8 h. The formation of CuNPs and size were confirmed by UV/Vis analysis and TEM imaging respectively. The experiment result showed that, 7.062 mM of hydrazine solution and 0.0147 mM of Cu2+ solution were needed to synthesize narrow size monodisperseCuNPs.The presence of nanoparticle was found after an induction period of 4 h and further reaction time, complete Cu0 state nanoparticle was obtained as deep red wine colour was observed. Stability study of CuNPs showed that the nanoparticles were stable up to 4 days. The particle size of the nanoparticles have been analysed by transmission electron microscopy (TEM) and the average size of CuNPs was in the range 2 to 10 nm.